Feasibility Study Development Of Randugunting Dam By Taking Larap Factor (Land Aquisition and Resettlement Action Plan) - Muji Rifai; Pratikso Pratikso; Soedarsono Soedarsono (International Conference on Coastal and Delta Areas, 2017)
Water is an essential ingredient for food availability, health and survival. Dams is one form of building in an effort to conserve water resources. The Randugunting Dam Development Plan in Blora Regency enters into 65 priority Dam in NAWACITA. Then to determine a project is feasible to be implemented or not, feasibility studies should be undertaken so that the business or project that is run not be in vain in the future. Any proposed public or private program or activity that is beneficial to the public interest and will result in an impact on 200 or more persons and requires compensation, it should be supplemented with a Land Acquisition and Resttlement Action Plan (LARAP) the policy covers: 1) Land acquisition and / resettlement should be avoided or minimized as far as possible; 2) If procurement of land is inevitable, the compensation provided and the transfer of the PAP should be accompanied by coaching efforts; 3) WTD receives appropriate compensation based on calculated replacement cost of affected assets; 4) In determining the amount of compensation value should be based on consultation and discussion with WTD. The cost components of the Randugunting Dam Development include pre-construction costs (land planning and acquisition / LARAP), construction costs and maintenance operation costs. Benefit components are viewed from the parties concerned with the project, especially for people in need including agriculture, fisheries, raw water, flood control, electricity and tourism. Development cost of Randugunting Dam with investment of Rp. 861.714.687.361 for 50 years. In view of the calculation results, NPV can be concluded of 139.866.838.506> 0 then the NPV is acceptable. The rate of return with the interest rate of 11.63% then the value of IRR of 11.63%> of DF = 10.49% so that investment is feasible. With the age of 50 years reservoir with the value of BCR of 1.16> 1 then the dam construction is feasible. BEP (Break Even Point) of the analysis produces BEP in the 30.4 year. Keywords: Feasibility Study, LARAP, Dams